What Explains the Stagnation of Female Labor Force Participation in Urban India? - Stephan Klasen; Janneke Pieters (Institute for the Study of Labor (IZA), 2013)
We study the surprisingly low level and stagnation of female labor force participation rates in urban India between 1987 and 2009. Despite rising growth, fertility decline, and rising wages and education levels, women's labor force participation stagnated at around 18%. Using five large cross-sectional micro surveys, we find that a combination of supply and demand effects have contributed to this stagnation. The main supply side factors were rising household incomes, husband's education, stigmas against educated women engaging in menial work, and falling selectivity of highly educated women. On the demand side, employment in sectors appropriate for educated women grew less than the supply of educated workers, leading many women to withdraw from the labor force.
Keywords: J20; J16; I25; O15; 330; female labor force participation; education; India